2015
DOI: 10.1186/s13012-016-0442-2
|View full text |Cite
|
Sign up to set email alerts
|

Sustained effectiveness of a multifaceted intervention to reduce potentially inappropriate prescribing in older patients in primary care (OPTI-SCRIPT study)

Abstract: BackgroundPotentially inappropriate prescribing (PIP) is common in older people in primary care and can result in increased morbidity, adverse drug events and hospitalisations. We previously demonstrated the success of a multifaceted intervention in decreasing PIP in primary care in a cluster randomised controlled trial (RCT).ObjectiveWe sought to determine whether the improvement in PIP in the short term was sustained at 1-year follow-up.MethodsA cluster RCT was conducted with 21 GP practices and 196 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 33 publications
0
44
0
6
Order By: Relevance
“…Исследователи рассчитывали смертность на 100 человеко-лет: самой высокой она оказалась в третьей и четвертой группах: 5,6 (95% ДИ 5,51-5,61) и 5,45 (95% ДИ 5,41-5,49), соответственно. В общей когорте смертность на 100 человеко-лет составила 5,08 (95% ДИ 5,05-5,11), во второй группе -4,40 (95% ДИ 4, 45). Также риск смерти зависел от продолжительности лечения ИПП.…”
Section: депрескрайбинг ингибиторов протонной помпы у пациентов пожилunclassified
See 3 more Smart Citations
“…Исследователи рассчитывали смертность на 100 человеко-лет: самой высокой она оказалась в третьей и четвертой группах: 5,6 (95% ДИ 5,51-5,61) и 5,45 (95% ДИ 5,41-5,49), соответственно. В общей когорте смертность на 100 человеко-лет составила 5,08 (95% ДИ 5,05-5,11), во второй группе -4,40 (95% ДИ 4, 45). Также риск смерти зависел от продолжительности лечения ИПП.…”
Section: депрескрайбинг ингибиторов протонной помпы у пациентов пожилunclassified
“…[28] было включено 21 исследование, в котором изучались результаты депрескрайбинга ИПП у пожилых пациентов ( ≥65 лет). В 6 исследованиях была подтверждена эффективность депрескрайбинга [44][45][46][47][48][49]. По мнению авторов обзора [28], вмешательство будет эффективным, если объяснить пациенту пользу депрескрайбинга и заинтересовать его.…”
Section: доказательная база депрескрайбинга иппunclassified
See 2 more Smart Citations
“…To this end, a cluster randomized controlled trial (RCT) was conducted to evaluate a multifaceted intervention, incorporating academic detailing with a pharmacist and medicines' review with web-based pharmaceutical treatment algorithms, to reduce potentially inappropriate prescribing among older people (10)(11)(12)(13). In the clinical effectiveness analysis the results indicated that, relative to usual care, the intervention was associated with a significant reduction in PIPs overall, largely driven by modifications to the prescribing of proton pump inhibitors (10,13). In addition to clinical effectiveness, any decision regarding the adoption of healthcare interventions in clinical practice should depend upon their expected cost effectiveness (14).…”
Section: The Opti-script (Optimizing Prescribing For Older People In mentioning
confidence: 99%